Hydroallantois In A Jafarabadi Buffalo: A Case Report - Hadiya, K.K.; Mungad, K.S.; Borkhatariya, D.N.; Kalasariya, R.M.; Dhami, A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Hydroallantois is one of the sporadic gestational disorders of dairy animals in which sudden increase in allantoic fluid occurs in allantoic cavity due to pathology of foetal membrane leading to bilateral enlargement of abdomen during late gestation (Roberts, 1971). It accounts for about 80-90 per cent of uterine hydrops and is characterized by a rapid and excessive accumulation of watery, amber coloured fluid inside the allantoic cavity over a period of 5 to 20 days giving suspicion for twin/multiple pregnancy (Sloss and Dufty, 1980; Morrow, 1986; Selvaraju et al., 2012). This condition invariably results in fetal gestational accident owing to placental dysfunction and fetal kidney failure (Arthur et al., 1996; Jana and Ghosh, 2012). This communication places on record of a rare case of hydroallantois in a Jafarabadi buffalo around 8 months of gestation and it’s medical management.